THE BURDEN IN THE PRIMARY CAREGIVERS OF ALZHEIMER PATIENTS - Roig, Mª Vicenta; Abengózar Torres, Mª Carmen; Serra Desfilis, Emilia (Anales de Psicología / Annals of Psychology, 1998)
This present study measures the burden experienced by the primary caregivers of Alzheimer patients. The sample is composed of 52 subjects of both sexes who had the following characteristics: they were 20 years old or older (there was no upper age limit), primary caregivers of elderly Alzheimer patients, the caregiver lived in the same household as the patient, the caregiver and the patient performed their daily rutine together. At last, the patients were not candidates for institutionalization. The variables that were controled were: age, sex, marital status, number of children, level of education, relation to the patient, time dedicated to the patient´s care, and the stage of development of the dementia (CAMDEX), as soon as the subject´s answers to a questionaire dealing with the burden experienced by de caregivers of elderly patients suffering from dementia (SCAD). The results of this study show that the caregivers who are women, 56 years old or older,married, with one child, with an average to low level of education, of low economic status, who have been caring for the patient for aproximately 10-12 years and who care for patients who are in the third fase of de disease experience the most burden.